Representing the Unpresentable: Historical Images of National Reform from the Qajars to the Islamic Republic of Iran by Negar Mottahedeh (Syracuse, New York: Syracuse University Press, 2008. 237 pages.) (American Journal of Islam and Society, 2009)
Negar Mottahedeh’s book contains an important analysis of the relationshipbetween Babism and modernity in Iran. The author argues that in order tounderstand “the historical conditions for Iranian perceptions of modernity”(p. 236), scholars need to break away from traditional disciplinary systems,just as Babism itself went against traditional understandings of Shi`ism inIran. It is a complex, highly reflexive, and ambitious proposal. The book’sdetailed historical account of the emergence of the Bab and the critical lensthrough which the author analyzes the impact of Qurrat al-Ayn Tahirih’s figureon the Iranian perceptions of the modern woman are bound to inspireany serious student of Iranian modernity. The figures of the Bab and Qurratal-Ayn Tahirih are analyzed against the backdrop of the deeply ingrained images of the ta`ziyeh, Fatimah, and Joseph, as well as Qur’anic images ofParadise and houris in Iranian culture. I have come away with a deeperunderstanding of the Iranian psyche and cultural attitudes toward modernitywith their unfathomable embrace of traditional and religious motifs.The book’s underlying questions are “Why are modern acts, often articulatedin terms of dress or veiling, associated with the dissent of the Babi?And why does this image of ‘the Babi’ appear as a dialectic of modernity,fluctuating between images ofWestern secularism and unveiling on the onehand, and as unpresentable images of Shi`ite antiquity, on the other?” (p.236). The reader does not get an answer addressing either the “why,” identifyingthe causes for this phenomenon, or an ethnographic account of howmodern Iranian society grapples with the antique elements of Shi`ite Islamicthought. Instead, the author sets out to map the influences of the ta`ziyeh onIranian cultural modernity in an “anti-disciplinary” fashion – just as Babismshould be understood in relation to Shi`ite thought infused with Iraniannationalism ...